The Hot, the Cold and the Lukewarm: Exploring the Depth and Determinants of Public Closeness to the African National Congress. (4th May 2018) - Gordon, Steven Lawrence; Struwig, Jarè; Roberts, Benjamin
ABSTRACT: South African politics has been dominated by the African National Congress (ANC) since the country's successful transition to democracy. But what is the degree of ANC support in South Africa at the micro-level? This paper will examine individual party closeness to the ANC for the period 2008–2014. We will use data from the nationally representative South African Social Attitudes Survey. Multivariate tests will be employed to identify the determinants of party closeness at the start of this period and at the end. Of those factors that our models revealed as statistically significant predictors of ANC support, the strongest was race group. Class identity, by contrast, was not strongly correlated with support. Interestingly, perceptions of electoral instrumentality were positively associated with higher levels of support for the ruling party. The findings of this paper suggest the need for future research on party closeness in the country and we conclude by outlining potential avenues of study.